2024
DOI: 10.1371/journal.pone.0300875
|View full text |Cite
|
Sign up to set email alerts
|

Anna Karenina as a promoter of microbial diversity in the cosmopolitan agricultural pest Zeugodacus cucurbitae (Diptera, Tephritidae)

Nele Mullens,
Wouter Hendrycks,
Jackline Bakengesa
et al.

Abstract: Gut microbial communities are critical in determining the evolutive success of fruit fly phytophagous pests (Diptera, Tephritidae), facilitating their adaptation to suboptimal environmental conditions and to plant allelochemical defences. An important source of variation for the microbial diversity of fruit flies is represented by the crop on which larvae are feeding. However, a “crop effect” is not always the main driver of microbial patterns, and it is often observed in combination with other and less obviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 102 publications
0
2
0
Order By: Relevance
“…AKP would be beneficial under changing environmental conditions as it would maximize chances that suitable bacteria, occurring within the microbial pool, could contribute to the insect responses to stress [ 33 ]. Studies have shown that the gut of Lepidoptera larvae harbors abundant microorganisms, particularly bacteria [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AKP would be beneficial under changing environmental conditions as it would maximize chances that suitable bacteria, occurring within the microbial pool, could contribute to the insect responses to stress [ 33 ]. Studies have shown that the gut of Lepidoptera larvae harbors abundant microorganisms, particularly bacteria [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the abundances of Enterococcus and Pseudomonas decreased. Notably, the multivariate dispersion of microbial patterns is significantly higher under these stressful environmental conditions [ 33 ]. In this study, we found that the dispersion level was higher in the 1:0 and 0:1 groups than in the 9:1, 1:1, and 1:9 groups ( Figure S2 ), implying that the pressure of individual infection by M. rileyi and B. bassiana was greater than that of the mixed group.…”
Section: Discussionmentioning
confidence: 99%